2008
DOI: 10.1088/0957-4484/19/36/365705
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence enhancement of SiGe/Si multiple quantum wells through nanowall structures

Abstract: The enhancement of light extraction from Si(0.5)Ge(0.5)/Si multiple quantum wells (MQWs) with nanowall structures fabricated by electron cyclotron resonance (ECR) plasma etching is presented. It is shown that the ECR plasma treatment does not damage the crystalline quality. At a driving current of 5.5 × 10(6) A m(-2), the light output intensity of the MQWs with nanowall structures shows an enhancement of about 50% compared with that of the original MQWs. In addition to the enhanced light extraction, the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…2d , for the as-grown MQW sample, the peaks at 230, 302, 417, and 437 cm −1 are assigned to Si(2TA) L , Si(2TA) X , Si-Ge phonon mode, and Si-Si phonon (local) modes, respectively. For the ICP-etched samples, both peaks of Ge(LO) and Si-Ge mode have a redshift compared to the as-grown MQW sample, which is mainly resulting from the compressive strain relaxation [ 13 ]. The Raman results prove that the crystalline quality of the ICP-etched samples was not damaged during the etching process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d , for the as-grown MQW sample, the peaks at 230, 302, 417, and 437 cm −1 are assigned to Si(2TA) L , Si(2TA) X , Si-Ge phonon mode, and Si-Si phonon (local) modes, respectively. For the ICP-etched samples, both peaks of Ge(LO) and Si-Ge mode have a redshift compared to the as-grown MQW sample, which is mainly resulting from the compressive strain relaxation [ 13 ]. The Raman results prove that the crystalline quality of the ICP-etched samples was not damaged during the etching process.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, they also pointed out that the real mechanisms for the PL enhancement were still not clear. The Chen group fabricated a randomly positioned SiGe/Si multi-quantum-well (MQW) nanowall by using electron cyclotron resonance plasma etching on an as-grown SiGe/Si MQW, and the measured electroluminescence intensity of the SiGe/Si MQW nanowalls increased to about 1.5 times for the enhancement of emission light extraction [ 13 ]. Chen et al also observed PL emission enhancement in size-uncontrollable Si/Ge superlattice pyramidal nanodots, which were fabricated by chemical selective etching through a self-assembled Ge QD mask [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques including laser- [40] and metal-assisted [41] chemical etching have been reported to fabricate ‘black silicon’ with an ultra-low reflectance. The surface nanoroughening process in this study could be an alternative approach applied to SiGe-based nanodevices and optoelectronics, such as metal-oxide-Si tunneling diodes [42], light-emitting diodes [25], and photodetectors operating in the telecommunication range [28]. In addition, the SiGe/Si MQW nanopits and nanorods with well-defined spatial periodicity fabricated in this study would also be potential materials applied to photonic crystals [1] and phototransistors [43].…”
Section: Resultsmentioning
confidence: 99%
“…Chen also fabricated pyramidal nanodots that possess Si/Ge SLs by chemical selective etching through a self-assembled Ge QD nanomask and found an obvious enhancement in PL emission [24]. In addition, an improvement of light extraction from SiGe/Si MQWs with nanowall structures fabricated by electron cyclotron resonance plasma etching through a random Al-masked pattern was also reported [25]. However, few studies reported the fabrication of periodic nanostructure arrays composed of SiGe/Si MQWs using NSL.…”
Section: Introductionmentioning
confidence: 99%